Optimizing GaN (112‾2) hetero‐epitaxial templates grown on (101‾0) sapphire. Issue 1 (31st August 2015) - Pristovsek, Markus; Frentrup, Martin; Han, Yisong; Humphreys, Colin J.
Abstract: The hetero‐epitaxy of ( 11 2 ‾ 2 ) GaN on ( 10 1 ‾ 0 ) sapphire was optimized in metal–organic vapor phase epitaxy. Best results were obtained from an AlN nucleation followed by AlN and AlGaN layers, and inserting low‐temperature AlN interlayers (ILs) as well as a SiNx IL. X‐ray diffraction (XRD) of ω scans of the symmetric ( 11 2 ‾ 2 ) reflection yielded an ω FWHM < 450 ″ along [ 11 2 ‾ 3 ‾ ] and < 900 ″ along [ 10 1 ‾ 0 ] together with a 100 × 100 μ m 2 rms roughness below 10 nm as determined by atomic force microscopy. The lowest threading dislocation density achieved was ≈ 10 9 cm − 2 while the basal plane stacking fault density was in the lower 10 5 cm − 1 range as determined by transmission electron microscopy. The suppression of the unwanted ( 10 1 ‾ 3 ‾ ) phase was lower than 1 in 10, 000 as judged from XRD.